Evaluation of localized flux and loss distribution in the corner joint and T joint of 1000 kVA transformer core - Shahanom, Uthman
The work involved in this thesis relates to the measurement and evaluation on localized flux and losses distribution in 1000 kVA three phase transformer core using 3% silicon doped Grain Oriented (GO) material. The experiment was carried out on three (3) type of transformer core models namely the 45° V notch T joint with 3mm overlap distance, 45° V notch T joint with 5mm overlap distance and 90° butt lap T joint design with 10 mm overlap distance. Measurement work dealt with variation of the magnitude and directional of the fundamental components as well as the harmonic components. Power loss measurement was conducted using three phase no load loss method. A few array of search coils made up of orthogonal, single turn and normal search coils were used to detect the in-plane and normal flux. Thermometric method adopting variation of temperature rise was selected to capture the power loss. The V notch T joint 3mm overlap design had shown the lowest power loss at 0.845 W/kg at 1.5T 50Hz compared to the V notch T joint 5mm overlap and butt lap 10mm design with difference of 1.3% and 5.79% respectively. Building factor of the V notch 3mm proved to be the lowest compared to the other two design which is at 1.11,1.15 and 1.185. It was noticed highest flux values were concentrated in the inner overlap area of the corner joint. Highest losses are spotted at the same location where highest inplane flux was presented. The third harmonic flux are highest in the butt lap T joint area. Rotational flux and losses were also detected in corner joint and very significant existence in the T joint area and butt lap design had produced the highest core loss at 0.894 W/kg. Highest core loss is located in the T joint area near both side of the inner corner of the center limb. The flux transfer works between lamination in a complex manner in which a combination of in-plane and normal flux move simultaneously within the laminations. Core geometry design and overlap distance is believed to be the critical factors that can influence the flux flow uniformity which ultimately can reduce power loss in the core. All in all V notch T joint 3mm core design is found to be the most efficient and with optimum performance. It is estimated that a saving of RM69.9 million per year can be achieved if the V notch T joint 3mm core design is utilized in TNB distribution network system.